Destination brand identity as a mediator between accessibility and tourist perception: Promoting Bama Yao as potential wellness tourist destination in China - Yan, Linwei; Alagas, Elangkovan Narayanan; Jambulingam, Manimekalai; Wang, Lei (Turyzm/Tourism, 2024)
This study aims to examine the impact of accessibility and destination brand identity on Chinese wellness tourist perceptions. It considers Bama Yao autonomous district’s growth towards longevity tourism and contributes to empirical work on the Chinese wellness tourism market. This quantitative research incorporated a post-positivism paradigm with the non-probability convenience sampling method to collect paper-based questionnaires: a total of 346 were coded for data analysis. The results demonstrated that accessibility positively influenced destination brand identity and tourist perceptions. Equally destination brand identity positively influenced tourist perception. Meanwhile, destination brand identity mediated the relationship between accessibility and tourist perception for wellness tourism destinations. However, the cross-sectional study’s results cannot be generalizable, and the sample may be one of its limitations. The present study provides policymakers and practitioners with the theoretical and practical basis to understand and predict tourists’ perceptions of wellness tourism destinations in China.